Pain management in preterm neonates using melatonin as an analgesic and antioxidant: a randomized clinical trial - Ghada Ibrahim Gad; Mai Essam Elsaeed Elattar; Heba Hassan Aly Osman; Hebatallah Ali Shaaban (The Egyptian Journal of Neurology, Psychiatry and Neurosurgery)
Abstract Background Preterm infants experience intensified pain perception compared to full-term ones due to immature inhibitory circuits and limited modulation. Pain arises from proinflammatory cytokines and oxidative stress. Growing evidence suggests that melatonin plays a crucial role in pain modulation through various mechanisms. This study aimed to assess melatonin’s analgesic effect during venous cannula insertion in preterm neonates using the Revised Premature Infant Pain Profile (PIPP-R) score before and after the procedure, and exploring the relation between procedural pain, oxidative stress, and the effect of melatonin by measuring serum Malondialdehyde (MDA) 60 min post-procedure. Results This randomized double-blind, interventional controlled clinical trial was conducted on 40 stable preterm infants < 37 week gestational age requiring peripheral intravenous cannula insertion were randomly assigned to two groups. The treatment group (MT, n = 20) received oral melatonin (5 mg/kg) dissolved in 2 ml distilled water 30 min before cannula insertion, while the placebo group (PL, n = 20) received 2 ml of distilled water as a placebo. In the present study, 60 min post-cannula insertion, MDA levels were significantly higher in the PL group compared to the MT group (p < 0.001). The PL group had significantly higher PIPP-R scores, and greater percentage of change in PIPP-R scores compared to the MT group, 5 min after cannula insertion. Conclusions Oral melatonin is a safe and effective therapy for preterm infants, showing promise in controlling neonatal pain with antioxidant effects, as indicated by decreased MDA levels.